Electrophysiological, structural, and functional disorders in patients with inflammatory cardiomyopathy secondary to inflammatory myopathy. Issue 4 (20th February 2022) - Liu, Yingxian; Hsu, Jeffrey; Liu, Xiaohang; Lin, Xue; Zhu, Yanlin; Jia, Fuwei; Wu, Wei; Chen, Wei; Wang, Qian; Fang, Ligang
Abstract: Background: Inflammatory cardiomyopathy (IC) is a syndrome with chronic myocarditis and cardiac remodeling. This study aimed to explore predicting factors of adverse outcomes in patients with IC secondary to idiopathic inflammatory myopathy (IIM‐IC). Methods: By means of a single‐center retrospective study, 52 patients with IIM‐IC at Peking Union Medical College Hospital were identified from January 1999 to June 2019. Electrocardiogram and echocardiography data were analyzed for the primary outcome (defined as all‐cause death) and secondary outcomes (defined as re‐hospitalization of heart failure and all‐cause death), using regression and survival analysis. Results: The prevalence of atrial fibrillation, ventricular tachycardia, Q‐wave abnormality, left ventricular conduction abnormalities, and reduced left ventricular ejection fraction (LVEF) (≤40%) were 65.4%, 67.3%, 67.3%, 61.6%, and 50.5%. After a median follow‐up of 2 years (IQR 0.8–3.0), 26 cases were readmitted due to heart failure. Twenty‐two deaths were recorded, including 20 cardiogenic deaths. Among the patients with adverse events, the incidence of poor R‐wave progression, low‐voltage of the limb leads, Q‐wave abnormality, QRS duration >130 ms, left ventricular enlargement, and impaired systolic function were higher. Kaplan–Meier analysis showed that Q‐wave abnormality, limb leads low‐voltage, LVEF ≤40%, and left ventricular end‐diastolic dimension >60 mm were correlated with shorter survival. However, multivariate Cox regression analysis revealed that only Q‐wave abnormality ( HR  = 12.315) and LVEF ≤40% ( HR  = 5.616) were independent risk factors for all‐cause death. Conclusion: Q‐wave abnormality and reduced LVEF are predictive of poor prognosis in patients with IIM‐IC. Abstract : Systemic evaluation of IC in patients with IIM.